Eventos extremos de chuvas em Barra dos Coqueiros/SE : circunstâncias e resiliências - Duarte, Thiago Lima Santana (2022)
The study of urban climate (Monteiro, 1976), in its rhythmic analysis, has served as a reference to understand how changes in the socio-spatial dynamics of urban areas reach the atmospheric systems, and how their effects affect, above all, life in society (and vice versa). Located on the coastal strip of the state of Sergipe, the municipality of Barra dos Coqueiros, the focus of this study, has its urban space expanded since the 2000s, and remains today, attracting economic activities, services, and especially migrants motivated by real estate speculation. With a predominantly hot and humid tropical climate, the occurrence of extreme rainfall events concentrated in the fall and winter is motivated by the influence of the eastern wave disturbances (DOLs) and the Antarctic polar mass; as a consequence, precipitation produces flooding points throughout the urban site due to the relatively flat topography. Being bordered by the Sergipe, Pomonga, and Japaratuba rivers, the influence of the ebb and flow of the ebb tides also contributes to the occurrence of floods in the city. In view of this situation, arising from urbanization and flaws in the drainage network (a factor that prevents the runoff of accumulated rainfall), the population is exposed to hybrid risks that intensify in socially and environmentally vulnerable spaces occupied by inhabitants with lower socioeconomic standards. In this sense, we mention the risks of flooding for those who live in the central region and in specific places in the neighborhood Atalaia Nova; also the risks of overflowing and of pathologies by contamination of the waterway of the population who live along the Guaxinim canal; as well as the risks of flooding, landslides, pathologies, in addition to the loss of property, safety and life itself of those who live in the semi-structured periphery of the city, in the sectors Atalainha and Travessa dos Pedreiros. From this context, we highlight the perception of the residents in relation to the climate and the impacts on the city's spaces and on daily social life. In this case, rainfall is seen as a problem for some of the inhabitants. It is worth mentioning that resilience measures were adopted to manage the crisis (such as the demolition and subsequent cleaning of the debris resulting from irregular shelters in the Travessa dos Pedreiros sector; as well as the dredging of the river channel in the sector Atalainha, where untreated effluents and domestic waste were discharged) and those that should be applied to mitigate the hybrid risks (such as the relocation of families from the high and very high risk areas to the low risk area, with the construction of the Governador Marcelo Déda residential complex, as well as environmental education activities through the replanting of mangrove and sandbank native seedlings, and through the effective operation of the garbage collection services). In order to reach the objectives and to measure the results, we tried to make use of a quali-quantitative methodology with a systemic basis, whose procedures highlight the issues of this research. This was done through a theoretical review, a cartographic survey, historical documentation, and field work (with photographic and newspaper records, the application of questionnaires, and data collection from the competent agencies). As a perspective, this study serves as an example for other smaller cities comparable to Barra dos Coqueiros. Thus, it is suggested that such cities be analyzed with academic rigor, by dedicating special attention to the assessment of vulnerabilities and, above all, to the environmental perception perceived by the residents in face of the problems they experience.